2021
DOI: 10.3390/children8080626
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns, Weight Perception and Obesity Status, among 10–12-Year-Old Children; an Epidemiological Study in Greece

Abstract: Adherence to certain dietary patterns influences obesity status in both children and adults. Weight perception influences dietary habits. The aim of this study was to examine children’s dietary habits and obesity status, in relation to weight perception. One thousand seven hundred Greek students enrolled in this study during 2014−2016. Children’s characteristics were assessed through validated questionnaires, and weight status was classified according to the criteria of the International Obesity Task Force. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Nutrition together with diet are major health determinants, while COVID-19 has had an intense impact on the adolescents’ dietary habits [ 14 ]. An unhealthy dietary pattern can lead to future negative health outcomes like overweight or obesity [ 15 ], cardiovascular diseases, diabetes, [ 16 ] and lower HRQoL [ 17 ]. On the other hand, adhering to a quality diet and adopting healthy eating habits provides a series of health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition together with diet are major health determinants, while COVID-19 has had an intense impact on the adolescents’ dietary habits [ 14 ]. An unhealthy dietary pattern can lead to future negative health outcomes like overweight or obesity [ 15 ], cardiovascular diseases, diabetes, [ 16 ] and lower HRQoL [ 17 ]. On the other hand, adhering to a quality diet and adopting healthy eating habits provides a series of health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The early identification of children with wrong weight perception, along with the promotion of healthy dietary habits, is of crucial importance from a public health perspective to combat childhood obesity. [17] The findings presented in the papers demonstrated that it is possible to design environmental-friendly meals from existing school menus. Legumes and pasta are often included, and white meat is selected instead of red meat.…”
Section: Discussionmentioning
confidence: 96%
“…Also, they are the ones that will be a key factor for the family, leading them to modify their eating behavior and change their general way of life [ 40 ]. Actually, it is crucial for parents to accurately identify their child’s weight status to prevent obesity [ 41 ].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%